Environmental Factors That Affect the Sanitary and Nutritional Variability of Raw Milk in Dual Purpose Livestock Systems of Colombian Orinoquia - Mauricio Vélez-Terranova; Rómulo Campos Gaona; Arcesio Salamanca-Carreño; Ricardo Andrés Velasco Daza; Brandon Alexis Arenas Rodríguez; José Sebastián Chaparro Ortegón (Animals, 2023)
Milk is the natural food with the highest biological quality for the human population and its production can be affected by several sanitary factors and management conditions. With the objective of identifying influence factors on milk compositional and sanitary quality in a region with wide productive potential in the Colombian Orinoquia, an experiment was carried out in two contrasting climatic seasons. For the milk compositional analysis, samples of daily production from 30 dual-purpose systems were analyzed. Similarly, the udder sanitary status of 300 cows was studied using the California Mastitis Test (CMT). Data analysis included mixed models, Pearson correlations, frequency tables, and the Kruskal–Wallis test. The results showed that the total daily milk production of the farm and the season influenced the milk compositional quality. The farms with milk productions lower than 100 kg/day presented the highest levels of protein, lactose, solid non-fat (SNF), and density, while in the rainy season, the milk quality was higher compared to the dry season. The CMT test indicated that only 7.6% of the evaluated mammary quarters presented two or more degrees of positivity. There is an opportunity to improve the milk compositional quality by improving the nutritional offer for animals during the year. The low CMT positivity indicates that, in the calf-at-foot milking system, the presence of subclinical mastitis is not a determining variable in milk production.